Analysis of the Use of Problem Based Learning Models in Independent Curriculum Learning - Sikumbang, Syilfy Adha (JMEA : Journal of Mathematics Education and Application, 2024)
This investigate points to depict how the Issue Based Learning learning demonstrate is utilized in free educational modules learning. To what degree is the utilize of PBL actualized within the learning prepare and what affect is delivered when utilizing the PBL show? This investigate strategy employments subjective inquire about strategies with a writing survey approach based on diaries. The inquire about stages were carried out beginning from article collection, article decrease, article show, dialog and conclusions related to the Issue Based Learning learning demonstrate and the free educational modules. The research data source is within the shape of diary articles taken from databases such as SINTA, Google Researcher, Measurements and other significant diary destinations. The comes about of the inquire about appear that the use of the Issue Based Learning learning show encompasses a critical affect with the normal increment in understudy learning results being over the KKM esteem. Problem-based learning coordinated at understudies is able to make strides basic considering abilities that can illuminate issues, so that it has an affect on expanding problem-solving capacities that make understudies able to fathom related issues. This is often in line with the goals of the autonomous educational programs.